The European Landscape Convention as a Tool for the Protection, Management and Planning of Landscapes - Adam Senetra; Monika Wasilewicz-Pszczółkowska; Elżbieta Grzelak-Kostulska (Barometr Regionalny)
Landscape protection and planning have attracted the attention of experts in many branches of science and industry. The growing interest in landscape management reflects concerns over environmental degradation that deteriorates the quality of life. Undesirable landscape changes result mostly from civilizational development, inappropriate land use and spatial planning. Further adverse landscape transformations should be prevented at local, regional and national levels. On 24 June 2004, Poland ratified the European Landscape Convention (ELC), which was opened for signature in 2000 in Florence (Italy ). The ratifying countries have committed themselves to enhance the quality of local landscapes which are the basic components of Europe’s natural and cultural heritage. Despite several attempts that resulted in the development of preliminary analytical reports, the Convention has not been implemented in Poland to date. For the Convention to be implemented, landscapes on Polish territory have to be identified and assessed. A systemized approach to landscape evaluation can provide a basis for creating landscape maps. This paper discusses selected methodological assumptions underlying landscape classification (typology ) and quality assessment, which could be used in the implementation process. The proposed method for assessing the esthetic value of landscape may become an integral part of landscape auditing, which is an important legal aspect of implementing the Convention. A landscape audit involves the identification of priority landscapes of particularly high scenic value.